A study on the hydrogeology and hydrogeochemistry of groundwater from different depths in a coastal aquifer: Annamalai Nagar, Tamilnadu, India - Chidambaram, S.; Senthil Kumar, G.; Prasanna, Mohan Viswanathan; John Peter, A.; Ramanathan, A.; Srinivasamoorthy, K. (Springer Berlin / Heidelberg, 2009)
Chemical characterization of groundwater is essential to bring out its nature and utility. Samples from shallow and deep ground water of the same location were collected and studied for their geochemical characteristics following standard procedures (APHA 1998). Sediment samples from different depths were collected and analysed for minerals using FTIR and SEM. Resisitivity logging was carried out in the bore well to understand the variations in depth to fresh water potential. The shallow ground water is dominated by Na-Cl-HCO3-SO4 and deeper groundwater by Na-HCO3-SO4-Cl types. It is observed that there is a significant ionic variation with depth. The ionic strength of the deeper samples is lesser than in the shallower samples. Wide pH variations in the shallow water samples are due to ion exchange process. Thermodynamic stability plot was used to identify the state of stability. It is inferred that there is no major significant difference in the thermodynamic state of stability in the shallow and the deeper aquifers as the aquifer matrix for the shallow and deeper aquifers are almost similar. Saturation index of Gibbsite, Kaolinite, Calcite, Dolomite and Anhydrite, were studied for shallow and deep aquifers, to identify the difference in hydrochemical signatures. The Si/Al ratios of shallow samples are less when compared with the deeper samples. Leaching of secondary salts was the chief mechanism controlling the ground water chemistry of the region.